Projected future changes in drought characteristics over Southeast Asia - Nguyen-Ngoc-Bich, Phuong; Phan-Van, Tan; Trinh-Tuan, Long; T. Tangang, Fredolin; Cruz, Faye; Santisirisomboon, Jerasorn; Juneng, Liew; Xiang Chung, Jing; Aldrian, Edvin (Vietnam Journal of Earth Sciences, 2022)
This study analyzes projected changes in drought characteristics over Southeast Asia for the mid and late 21st century under Representative Concentration Pathway (RCP) scenarios (RCP4.5 and RCP8.5) that participated in IPCC AR5. Drought characteristics are computed using the standardised precipitation index (SPI) with 12-month time scales based on precipitation data from the multi-model downscaled experiments of the Coordinated Regional Climate Downscaling Experiment-Southeast Asia (CORDEX-SEA). Comparison with observations indicates that model uncertainties are high over Myanmar, southern China, and some areas of the Maritime Continent. The multi-model ensemble is in best agreement with the observation relative to individual models. Under the future projections, the ensemble model exhibits no significant changes in duration and severity of drought for all scenarios in the mid 21st century. However, the drought characteristics are projected to become shorter and more severe for RCP8.5 in the late 21st century. Projected changes in inter-arrival time, maximum intensity, frequency, and geographic extent also indicate more frequent and severe drought over the mainland in the late 21st century for RCP8.5.